An Improved Evans Blue Staining Method for Consistent, Accurate Assessment of Plasmodiophora brassicae Resting Spore Viability - Harding, M W (Plant disease, 2019)
Clubroot caused by Plasmodiophora brassicae is an important disease of brassica crops. The use of vital stains to determine the viability of P. brassicae resting spores can provide useful information regarding spore longevity, inoculum potential, or the efficacy of antimicrobial treatments. Evans blue is one example of a vital stain that has been reported to differentially stain viable and nonviable resting spores. Some previously published protocols using Evans blue to stain P. brassicae resting spores have not provided accurate or consistent results. In this study, we modified the Evans blue method by increasing the staining time to 8 h or more and evaluated P. brassicae resting spores after heat treatment at various combinations of temperature and time. Extending staining times significantly increased the numbers of stained resting spores up to 7 h, after which the numbers of stained spores did not change significantly (R2 = 96.88; P ≤ 0.001). The accuracy of the modified method to discriminate viable and nonviable spores was evaluated in repeated experiments and by comparing the staining data with those derived from inoculation assays and propidium monoazide quantitative PCR (qPCR). The results demonstrated that the modified Evans blue staining method improved the accuracy and consistency of measurement of P. brassicae resting spore viability. Additionally, it was equivalent to the qPCR method for differentiating viable and nonviable spores (R2 = 99.84; P ≤ 0.001) and confirmed in canola infection bioassays